Digital Mapping Based on Geographic Information Systems for the Village Apparatus of Siabu: Pemetaan Digital Berbasis Sistem Informasi Geografis Untuk Aparatur Desa Siabu - Mildawati, Roza; Dewi, Sri Hartati; Fitrianti, Fitrianti; Adriati, Yolly; Annisa, Bismi; Arizona, Rafil; Astuti, Puji; Anggellika, Revina Evellyn; Febriani, Nadila (Universitas Lancang Kuning, 2024)
Spatial planning is already a standard government tool that is made periodically at the National, Provincial, District and even Village levels, however, this tool often loses its meaning and function due to inappropriate approaches and manufacturing processes. This is mostly caused by a lack of human resource capacity and skills, and mapping skills that have not been mastered by government officials at the basic level, including at the kelurahan and sub-district levels. It is necessary to present geospatial information using maps and disseminate it from the highest level of government to the lowest village/kelurahan level. As one of the administrative areas of Siabu Village, Salo District, Kampar Regency, it still has problems in conducting administrative mapping of its area due to the absence of competent personnel and the absence of digital mapping skills by utilizing geographic information system technology. This community service activity is to provide counseling regarding digital mapping based on geographic information systems for Siabu Village apparatus. The methodology for implementing this activity consists of the preparation, socialization, implementation and evaluation stages. By carrying out this counseling, it can help the surrounding community as well as provide information in the administrative mapping of the area in Siabu Village. For the next program, it is important to conduct counseling by directly surveying the condition of Siabu Village. Apart from that, the provision of a map of Siabu Village to Siabu Village Apparatuses is expected to help Siabu Village apparatus. By carrying out this counseling, it is hoped that the Siabu Village apparatus can understand digital mapping methods based on geographic information systems that can help the performance of Siabu Village apparatus.